Peningkatan Motorik Halus Anak Usia 3-4 Tahun Menggunakan Media Loose Parts dengan Teknik Token Ekonomi di Layanan Terapi Bintang Bunda Cerme - Muchammad Fajar Purdianto; Ima Fitri Sholichah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Early childhood education aims to develop motor, affective and life skills, not just creativity. Early age is a golden period that requires appropriate stimulation to optimize growth and development. One challenge is the development of fine motor skills, such as the ability to grasp at the age of 3-4 years (Antara, 2019). Loose parts media helps hone creativity and motor skills, as well as supports logic and concentration (Nurfadilah et al., 2020). To motivate children, the token economy technique is used, namely giving temporary prizes such as coins that can be exchanged (Hackenberg, 2018). This program is entitled: